If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -5x = 4x + 16 Reorder the terms: 1 + -5x = 16 + 4x Solving 1 + -5x = 16 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 1 + -5x + -4x = 16 + 4x + -4x Combine like terms: -5x + -4x = -9x 1 + -9x = 16 + 4x + -4x Combine like terms: 4x + -4x = 0 1 + -9x = 16 + 0 1 + -9x = 16 Add '-1' to each side of the equation. 1 + -1 + -9x = 16 + -1 Combine like terms: 1 + -1 = 0 0 + -9x = 16 + -1 -9x = 16 + -1 Combine like terms: 16 + -1 = 15 -9x = 15 Divide each side by '-9'. x = -1.666666667 Simplifying x = -1.666666667
| 3xsquared-10x=-1 | | 33c=726 | | 2(-4p-1)+(2.5-p)=x | | 5/2t-10=-30 | | 10x+30-20=90 | | 3.2b=1.8+3.6b | | f(x)=2x^3-8x^2+4x-16 | | 5y-2=28y | | 2b+42=7a+33 | | .25(r+8)=r-8 | | 4x+7x-4=56 | | 3x+12=-112 | | 4x+2=3x-16 | | s=2ab | | 4x+10+2x-20=90 | | 7(x-3)=3x+4x | | b^2-16b+70=0 | | 7b^2-b-6=0 | | x^2+y^2+19x-4y=0 | | 53+4b=11+2b | | b-28.2=5.7 | | 2t-11t= | | (5x-6)(x+1)= | | m/4-m | | 5a-1=19 | | -x-5(-7x+16)=22 | | 7t-30+t^2=0 | | 91000=35x^2-3640x+7000 | | 15+5x=-75 | | (2x+7)*(5x+9)= | | x/6-5=-3 | | 3/7x-1/3=-1/2 |